Adenosine A2A receptor mediated protective effect of 2-(6-cyano-1-hexyn-1-yl)adenosine on retinal ischaemia/reperfusion damage in rats. Issue 7 (13th April 2006) - Konno, T; Sato, A; Uchibori, T; Nagai, A; Kogi, K; Nakahata, N
Abstract : Aims: To determine the effect of 2-(6-cyano-1-hexyn-1-yl)adenosine (2-CN-Ado), an adenosine A2A receptor agonist, on retinal ischaemia/reperfusion damage in rats. Methods: Retinal ischaemia/reperfusion damage was induced by elevating the intraocular pressure of one eye to 130 mm Hg for 60 minutes and returning it to normal. 7 days later, retinal ischaemia/reperfusion damage was histologically quantified by measuring the thickness of retinal layers. Intraocular pressure was measured by pressure transducer. Results: Retinal ischaemia/reperfusion caused cell loss in the ganglion cell layer and thinning of the inner plexiform and nuclear layer. Both ocular topical and intravenous administration of 2-CN-Ado caused a reduction of retinal ischaemia/reperfusion damage. A selective A2A receptor antagonist, 1, 3, 7-trimethyl-8-(3-chlorostyryl) xanthine (CSC), but not a selective A1 receptor antagonist, 8-cyclopentyl-1, 3-dipropylxanthine (DPCPX), or a selective A2B receptor antagonist, alloxazine, reduced the protective effect of 2-CN-Ado. While ocular topical administration of 2-CN-Ado caused a sustained reduction of intraocular pressure, intravenous administration of 2-CN-Ado showed a transient ocular hypotensive effect. Conclusions: These results suggest that 2-CN-Ado attenuates retinal ischaemia/reperfusion damage, and at least some of this protective effect of 2-CN-Ado might be mediated via activation of the adenosine A2A receptor.